Optimizing wheat mix composition to maximize customer satisfaction - Oredola, Emmanuel (Kansas State University, 2024)
Imagine a flour miller with several customers producing different products. Each of them demands a unique flour to meet their customers’ needs. The miller receives wheat from numerous sources, each presenting very different compositions of protein, ash, and moisture holding capacity. It is the unique composition of these three components of flour that gives it its useability across numerous products. That is, different customers for the miller require flour that has idiosyncratic combinations of the foregoing attributes. The miller’s task is to meet each customer’s demand by offering flour that is exactly or close to what they need at a price they are willing to pay. Therefore, the miller’s challenge is not just to minimize cost of producing each specific flour but to get the highest possible margin from each customer. The purpose of this thesis was to optimize the cost of producing flour to the unique specification of each of the miller’s multiple customers and compare the profitability of each customer based on their offer prices and customers’ rheological specifications. The research used five customers as a case study based on a flour mill’s inventory of five types of flour. The results showed that customers’ rheological needs had a direct impact on the cost of the wheat required to produce the flour they needed. The results showed that while one customer’s (Customer 1) needs could be satisfied with a single type of wheat, Customer 3’s needs could only be satisfied using a blend of four types of wheat. Incidentally, the larger number of types of wheat needed did not imply higher cost. Customer 4 and Customer 5 needed three types of wheat to produce their rheological specification and Customer 5 had the highest cost per bushel of needed to produce their flour. The results revealed the wheat type that was not needed in any customer’s mix. This would suggest that if these were the total customer list of the miller, then wheat they were not needed to meet the lowest cost mix for any customer should not be procured. Therefore, this project could direct the procurement team to match their activities with the manufacturing team in sourcing and procuring only wheat they are needed in customer products. The research also noted the potential for future work that could segment customers into product groups to facilitate scale and in so doing enhance the profitability from specific mixes by not only reducing cost of producing particular mixes but to expand volume and revenues in order to maximize profits.
Keywords: Wheat; Blending; Optimization; Miller specifications; Flour; Costing